Increased Integrity of Plasma Membrane and Acrosome Cap Spermatozoa Limousin Cattle at Post Thawing in Frozen Media by adding Seawater Extract - Faidah, Nur; Hernawati, Tatik; Lamid, Mirni; Ismudiono, Ismudiono; Suprayogi, Tri Wahyu; Mulyati, Sri (KnE Life Sciences, 2017)
This research was determined membrane integrity and acrosome cap of Limousin bull post thawing after adding seawater extract with different concentrations in extender skim milk and egg yolk to increased frozen semen quality. This research used fresh samples of Limousin bull’s semen collected by using artificial vagina, then devided into 4 treatments and 6 replications. The experimental design that used was Complete Random Design. Analysis of the data using Analysis of Variant (ANOVA) one way then proceeds to the Duncan Multiple Range Test to determine significant differences between treatments.The first treatment P0 no seawater extract added as a control. The second treatment P1 was treated with 0.109 µL seawater extract, P2 was treated with 0.426 µL seawater extract, and P3 was treated with 1.09 µL seawater extract. The result showed that determine significant differences between treatments. The post thawing membrane integrity’s result was P0= 22.00 ± 4.28, P1= 22.66 ± 3.61, P2= 25.00 ± 2.75, and P3= 29.00 ± 1.67. The post thawing acrosome cap’s result was P0= 30.50 ± 1.37, P1= 31.50 ± 3.27, P2= 34.83 ± 2.31, and P3= 38.00 ± 1.41. The highest concentration added seawater extract to increased membrane integrity and acrosome cap spermatozoa in this research was 1.09 µL. Keywords: Limousin bull; spermatozoa; seawater extract; membrane integrity; acrosome cap